Transition metal and rare earth quad-doped photovoltaic phosphate glasses toward raising a-SiC:H solar cell performance. (17th November 2015) - Song, P; Zhang, C M; Zhu, P F
Abstract: Efficiency enhancement of a hydrogenated amorphous-silicon carbide (a-SiC:H) solar cell using downshifting and upconversion of photovoltaic (PV) glasses doped with transition metal (TM) ions and rare earth (RE) ions are investigated. P2 O5 -Li2 O-Al2 O3 -Sb2 O3 -MnO-Yb2 O3 -Er2 O3 glass doped with Sb 3+ -Mn 2+ -Yb 3+ -Er 3+ ions is prepared and the PV glass is placed on an a-SiC:H solar cell. The performance of the cell in combination with the PV glass is simulated and measured, and the results show that the theoretical and experimental efficiencies are both enhanced compared to the bare one. The potential of TM-RE quad-doped glasses for improving the efficiency of a-SiC:H PV modules are explored.